Robust and Reliable Broadcast Protocols in the Stand-Alone and Simulation-Based Frameworks - ZHU, Huafei (Institutional Knowledge at Singapore Management University, 2008)
The research on reliable communication in distributed networks has a rich history due to its fundamental importance. In this paper, an efficient implementation of reliable broadcast communications in the stand-alone and simulation- based framework is formalized and analyzed by means of sequential aggregate signatures. A reliable broadcast problem is called stand-alone if the security of broadcast protocols can be efficiently reduced to the security of the underlying digital signatures. A reliable broadcast is called secure in the simulation- based framework if it is provably secure in the universally composable paradigm. Our reliable broadcast protocol works in the unknown fixed-identity networks where no public key infrastructure (PKI) exists. We show that our implementation is robust in the sense that the proposed broadcast protocol can resist against up to k adversaries assuming that the underlying network is (2k + l)-vertex connected and individual signatures are secure against adaptive chosen-message attack.